Company restructuring across borders: with or without European Works Coucils? - De Spiegelaere, Stan (Brussels, 2017)
"This policy brief takes as its starting point the fact that as soon as a company engages in European-level transnational restructuring, transnational information and consultation is needed to enable the social partners to consider the cross-border dynamic of the planned measures. This policy brief addresses the following questions: How widespread is transnational restructuring in Europe? What is the role of EWCs in restructuring processes? How extensive is the transnational information and consultation coverage in companies involved in transnational restructuring? The authors present several policy recommendations including the need to make EWCs obligatory in companies of a certain size and provide them with better material, legal resources and access to expert advice."